Answer:
Solution -->
when x --> infinity the y goes to infinity too.
Explanation:
We have the eq.
with y(1) = 3. So a reconfiguration o this last one equation can be like:
so is of the form y'+p(x) y = f(x), where the integral factor is given by:
is,
Multiplying the whole equation with this integral factor we can write the expression:
and from this we obtain,
So when y(x=1) = 3, c = 2 and the complete solution can be writen as:
.
And we can see that when x --> infinity the second term of the solution is practically zero and the first is infinity so y also goes to infinity when x does.